Smartphone-Based Order Recording Application for Non-Technical Users: A Local Network Solution - Ade Bani Riyan; Mohamad Nasir; Septien Dwi Savandha; Ade Fitria Fatimah; Diana Magfiroh; Amelia Amelia (Politeknik Siber Cerdika Internasional, 2026)
Background: Digital technology adoption among micro, small, and medium enterprises (MSMEs) in Indonesia remains limited, particularly among non-technical users. Many existing commercial applications present barriers related to system complexity, subscription costs, and dependence on stable internet connectivity, which hinder effective business digitalization. Aims: This study aims to develop and evaluate a smartphone-based order recording application tailored to MSME users with limited digital literacy, focusing on accessibility, usability, and operational efficiency without reliance on internet infrastructure. Methods: The research employed a Research and Development (R&D) methodology with a mixed-methods approach. The development process followed five iterative stages: needs analysis involving 18 MSME owners, user-centered system design, technical implementation using a local area network architecture, functional and usability testing, and iterative refinement based on user feedback. Usability evaluation was conducted with 12 non-technical MSME users using task performance metrics and the System Usability Scale (SUS). Results: The application achieved a SUS score of 74.2, indicating good usability, with an average task completion rate of 91.7%, surpassing typical benchmarks for commercial MSME applications. The local network architecture successfully eliminated internet dependency, reduced operational costs, improved system responsiveness, and enhanced data privacy. Key usability factors included simplified interfaces, minimal text input, large touch targets, consistent navigation, and reduced cognitive load. Conclusion: The findings demonstrate that digital solutions designed around user capabilities can effectively bridge the digital divide among non-technical MSME users. This study provides a replicable model for inclusive, low-cost, and accessible business application development in resource-constrained contexts.